Pola Penggunaan Obat Antidiabetes di Puskesmas Grabag Magelang - Nurul Maulidya; Oktianti, Dian (Journal of Holistics and Health Science, 2021)
Diabetes Mellitus (DM) is a long-term or chronic disease which continues to increase every year. Indonesia itself is ranked 7th for the most DM sufferers in the world. The purpose of this study was to determine the profile of the use of antidiabetic drugs in DM patients at the Grabag Public Health Center. The method used in this research is descriptive method, with retrospective data collection. The population of DM sufferers at the Grabag Public Health Center was 50 patients, with the sampling technique using the total sampling method. The inclusion criteria were medical record data for outpatient type 2 diabetes mellitus, and the exclusion criteria incomplete medical record data. The results of this study were the use of oral antidiabetic drugs (OAD) with single therapy, metformin 32% and acarbose 2%, and with combination therapy are metformin + glimepirid 58%, acarbose + glimepiride 2%, and metformin + glimepiride+acarbose 6%. Based on the duration of suffering from diabetes, for 1 year the most people used metformin by 26%, for 2 and 3 years the most used metformin + glimepiride by 38% and 8%, while for 4 years using a combination of metformin + glimepiride + acarbose by 2%. Most of the patients are accompanied by hypertension complications. The most widely used single therapy oral OAD is metformin and the combination therapy is metformin + glimepiride. Patients suffering from diabetes for 1 year of treatment used metformin single therapy, for 2 and 3 years the most treatment used 2 combination therapy, glimepiride + metformin, while for 4 years of treatment using 3 combination therapy metformin + glimepiride + acarbose. Abstrak Diabetes Mellitus (DM) merupakan penyakit jangka panjang atau kronis yang pada setiap tahunnya terus mengalami peningkatan. Indonesia sendiri menduduki peringkat ke-7 untuk penderita DM terbanyak didiunia. Tujuan penelitian ini adalah untuk mengetahui profil penggunaan obat antidiabetes pada pasien DM di Puskesmas Grabag. Metode yang digunakan pada penelitian ini adalah metode deskriptif, dengan pengambilan data secara retrospektif. Populasi penderita DM di puskesmas Grabag sebanyak 50 pasien dengan teknik pengambilan sampel menggunakan metode total sampling. Kriteria inklusi berupa data rekam medik pasien DM tipe 2 rawat jalan, dan kriteria eksklusi berupa data rekam medik yang tidak lengkap. Hasil dari penelitian ini adalah penggunaan obat antidiabetes (OAD) oral dengan terapi tunggal yaitu metformin 32% dan acarbose 2%, dan dengan terapi kombinasi adalah metformin + glimepirid 58%, acarbose + glimepiride 2%, dan metformin+glimepiride + acarbose 6%. Berdasarkan lamanya menderita DM, selama 1 tahun terbanyak menggunakan metformin sebesar 26%, selama 2 dan 3 tahun terbanyak menggunakan metformin + glimepiride sebesar 38% dan 8%, sedangkan selama 4 tahun menggunakan kombinasi metformin + glimepiride + acarbose sebesar 2%. Sebagian besar pasien disertai dengan komplikasi hipertensi. Penggunaan OAD oral terapi tunggal terbanyak adalah metformin dan terapi kombinasi adalah metformin+glimepiride. Pasien yang menderita DM selama 1 tahun pengobatan terbanyak menggunakan terapi tunggal metformin, selama 2 dan 3 tahun pengobatan terbanyak menggunakan terapi 2 kombinasi yaitu glimepiride + metformin, sedangkan selama 4 tahun pengobatannya menggunakan terapi 3 kombinasi yaitu metformin + glimepiride + acarbose.